The equation for midpoint is
((x1+x2)/2 , (y1+y2)/2) = ((1+3)/2 , (-2+2)/2)
= ( 2,0)
Answer:
Step-by-step explanation:
A. abject - 2. wretched
B. congenial - 6. friendly
C. deliberately - 7. thoughtfully
D. impetuous - 3. impulsive
E. misgiving - 4. doubt
F. perturbation - 5. disturbance
G. pervade - 8. permeate
H. transgress - 1. err
Hope this helps :)
Answer:
Alright well Graph each side of the equation. The solution is the x - value of the point of intersection k = 4.582 Hope this helps :)
Step-by-step explanation:
To find the surface area, use this square pyramid surface area formula: Square Pyramid Surface Area = 2 x B x S + B 2 B = Width of the Square Base S = Slant length of one of the triangular faces and is calculated from the height and base width by using the equation: S= The square root of [(.5B) 2 + Height 2] .